Understanding global liquidity - Eickmeier, Sandra; Gambacorta, Leonardo; Hofmann, Boris 1972- (Bank for Internat. Settlements, 2013)
We explore the concept of global liquidity based on a factor model estimated using a large set of financial and macroeconomic variables from 24 advanced and emerging market economies. We measure global liquidity conditions based on the common global factors in the dynamics of liquidity indicators. By imposing theoretically motivated sign restrictions on factor loadings, we achieve a structural identification of the factors. The results suggest that global liquidity conditions are largely driven by three common factors and can therefore not be summarised by a single indicator. These three factors can be identified as global monetary policy, global credit supply and global credit demand.
Parallel als Online-Ausg. erschienen